Strengthening and permeability control in sand using Cr3+-crosslinked xanthan gum biopolymer treatment - Lee, Minhyeong; Chang, Ilhan; Park, Dong Yeup; Cho, Gye Chun (Transportation Geotechnics, 2023)
Trivalent chromium (Cr3+), commonly used in reservoir conformance control, has recently been introduced as an innovative technique for enhancing the strength and durability of Xanthan gum (XG) biopolymer-based soil treatment via Cr3+-induced crosslinking. We investigated the effects of Cr3+-crosslinked XG (Cr-XG) biopolymer treatment on the strength, stiffness and hydraulic conductivity of sand through a comprehensive series of experiments, including unconfined compression, direct shear, constant-head permeability tests, and rheological yield stress measurements. The results revealed that gelation of Cr-XG hydrogel via crosslinking between cation and carboxyl groups in XG, leading to gel stiffening, enhances cohesion within the sand over time. Furthermore, the increased yield stress in the Cr-XG hydrogel, compared to clean XG hydrogel, contributes to a more enduring pore-clogging effect, particularly under elevated hydraulic gradient conditions. The addition of 1% Cr-XG biopolymer to the sand significantly increased the ultimate bearing capacity by 466% and resulted in a four-orders-of-magnitude reduction in hydraulic conductivity, in comparison to untreated sand. This study elucidated the soil strengthening mechanism and efficacy attributed to crosslinking-induced gelation in Cr-XG biopolymer treatment. It effectively addressed limitations inherent in previous biopolymer-soil treatments, thereby accentuating its potential as a rapid grouting material within geotechnical engineering.
Keywords: Crosslinking gelation; Grouting material; Permeability reduction; Soil strengthening; Trivalent chromium; Xanthan gum biopolymer